KEANEKARAGAMAN BURUNG MIGRAN DI PESISIR PANTAI TIMUR KABUPATEN DELI SERDANG SUMATERA UTARA - Desi Yani Harahap; Pindi Patana; Rahmawaty Rahmawaty (Program studi Kehutanan USU, 2013)
Mudflat and mangrove ecosystem both are the migratory bird habitat. This research was counting the index of diversity migratory shorebirds East Coastal of Deli Serdang District, Province of North Sumatra. The result showed value average an index of diversity with medium category (H' 2.03). The highest diversity (H' = 2.12) was found at Bagan Percut and the lowest (H' = 1.94) found at Pantai Ancol. Included in medium category, the diversity of migratory shorebirds influenced by mudflat condition. Keywords: mudflat, migratory birds, mangrove, coastal area.